The postman always rings twice [videorecording (DVD)] - Garnett, Tay; Turner, Lana, 1921-1995; Garfield, John; Kellaway, Cecil, 1891-1973; Cronyn, Hume; Ames, Leon, 1902-1993; Cain, James M. (James Mallahan), 1892-1977 (Turner Entertainment : Distributed by Warner Home Video, 2004)
Frank Chambers (John Garfield) is a drifter who lands at a roadside gas station owned by jolly old Nick Smith (Cecil Kellaway) and his young, blonde wife Cora (Lana Turner). In a matter of minutes, Frank and Cora fall in love, and plot to murder Nick. Eventually wedding bells ring, the body count rises, and the gavel slams-of course, nothing ever goes as planned. Part of what makes the film noir is watching the characters react, as their plans are derailed one by one.